Ratio determination of solids and voids for traditional Malay carvings: a preparation for environmental performance - Abdul Majid, Noor Hanita; Denan, Zuraini (International Association of Computer Science and Information Technology Press (IACSIT Press), 2015)
Carvings in forms of openings, roof ends and walls have been incorporated as aesthetic and climatic element in the Malay traditional buildings. Determining the ratio of solids and voids on carvings elements is seen as an essential step to gain insight on the performance of carvings as a shading devices to control sunlight and air flow. The research objectives are to inventory and digitize the carvings to determine the ratio of solid and voids, and predict their performances. The carvings sampled from all states in Peninsular Malaysia are digitized using AutoCAd to determine the area of solid and void. The ratio of solid and voids ranges from 1:1 to 99:1 and the most common ratio are 3:2. The ratio study is a preliminary findings towards a detail study on the daylight and ventilation control in the traditional houses.